MALDI-TOF Mass Spectrometry Discriminates Known Species and Marine Environmental Isolates of Pseudoalteromonas - Emami, Kaveh; Nelson, Andrew; Hack, Ethan; Zhang, Jinwei; Green, David H.; Caldwell, Gary S.; Mesbahi, Ehsan (Frontiers in Microbiology, 2016)
The genus Pseudoalteromonas constitutes an ecologically significant group of marine Gammaproteobacteria with potential biotechnological value as producers of bioactive compounds and of enzymes. Understanding their roles in the environment and bioprospecting for novel products depend on efficient ways of identifying environmental isolates. Matrix Assisted Laser Desorption/Ionisation - Time of Flight Mass Spectrometry (MALDI-TOF MS) biotyping has promise as a rapid and reliable method of identifying and distinguishing between different types of bacteria, but has had relatively limited application to marine bacteria and has not been applied systematically to Pseudoalteromonas. Therefore, we constructed a MALDI-TOF MS database of 31 known Pseudoalteromonas species, to which new isolates can be compared by MALDI-TOF biotyping. The ability of MALDI-TOF MS to distinguish between species was scrutinised by comparison with 16S rRNA gene sequencing. The patterns of similarity given by the two approaches were broadly but not completely consistent. In general, the resolution of MALDI-TOF MS was greater than that of 16S rRNA gene sequencing. The database was tested with thirteen environmental Pseudoalteromonas isolates from UK waters. All of the test strains could be identified to genus level by MALDI-TOF MS biotyping, but most could not be definitely identified to species level. We conclude that several of these isolates, and possibly most, represent new species. Thus, further taxonomic investigation of Pseudoalteromonas is needed before MALDI-TOF MS biotyping can be used reliably for species identification. It is, however, a powerful tool for characterising and distinguishing among environmental isolates and can make an important contribution to taxonomic studies.